2017
DOI: 10.1111/exd.13382
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of serum markers of cellular immune activation in patients with bullous pemphigoid

Abstract: Experimental models of bullous pemphigoid (BP), the most frequent subepidermal autoimmune bullous disease, revealed that the immune response leading to blister formation represents an incompletely understood complex process involving different inflammatory cells. In contrast to previous reports commonly focusing on limited molecular and cellular phenotypes of the disease, the aim of this study was to investigate a broad spectrum of markers of cellular immune activation in patients with BP. We found that serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 42 publications
1
23
0
1
Order By: Relevance
“…This induced steroid insensitivity was previously demonstrated for chronically stimulated cells with pro‐inflammatory factors such as TNF‐α and IFN‐γ, two Th1 cytokine with elevated concentration in the blister fluid . More recently, both IL‐17 and IL‐23 were shown to increase the expression of GRβ in PBMC, which release soluble marker of immune activation . In this line, we recently demonstrated that IL‐17 and IL‐23 concentrations were elevated in the blister fluids of patients with BP and that sustained elevated concentrations of these cytokines in those patients were predictive of poor outcome .…”
Section: Discussionsupporting
confidence: 59%
“…This induced steroid insensitivity was previously demonstrated for chronically stimulated cells with pro‐inflammatory factors such as TNF‐α and IFN‐γ, two Th1 cytokine with elevated concentration in the blister fluid . More recently, both IL‐17 and IL‐23 were shown to increase the expression of GRβ in PBMC, which release soluble marker of immune activation . In this line, we recently demonstrated that IL‐17 and IL‐23 concentrations were elevated in the blister fluids of patients with BP and that sustained elevated concentrations of these cytokines in those patients were predictive of poor outcome .…”
Section: Discussionsupporting
confidence: 59%
“…Pro‐Inflammatory cytokines such as IL‐17 and the related cytokines including IL‐13 and IL‐22 play a role in the recruitment of neutrophil and eosinophils, with elevated levels correlating with relapse of disease. Other parts of the cellular immune system such as mast cells, complement, neutrophils, macrophages, T cells, and eosinophils are thought to be involved in the pathophysiology . The majority of cases are not associated with an identifiable trigger .…”
Section: Bullous Pemphigoidmentioning
confidence: 99%
“…Other parts of the cellular immune system such as mast cells, complement, neutrophils, macrophages, T cells, and eosinophils are thought to be involved in the pathophysiology. 18 The majority of cases are not associated with an identifiable trigger. 10 Drugs reported to trigger BP include diuretics (eg.…”
Section: Bullous Pemphigoidmentioning
confidence: 99%
“…160,162 Furthermore, a correlation of tryptase serum levels with disease activity was reported. 163 Interestingly, in addition to IgG, also IgE autoantibodies with the same or similar specificity are present in about 70% to 90% of patients with BP. 23,164 These findings suggest that MCs could be activated by FcεRI cross-linking by IgE-BP180 complexes.…”
Section: Autoimmune Diseasesmentioning
confidence: 99%